PENGARUH PEMBERIAN UPAH DAN INSENTIF TERHADAP PRODUKTIVITAS KERJA KARYAWAN PADA PT. INDONESIA EPSON INDUSTRY - Suryadi; Asmawati; Fitri Rahmawati; Qothrun Nada; Retta Dwiprajatie (Prosiding SEMANIS: Seminar Manajemen Bisnis, 2023)
Wages and Incentives are important elements in improving employee productivity. With the provision of appropriate wages and incentives, the productivity PT Indonesia Epson Industry it will be enhanced, so the company will be ready and able to compete with other companies in the face of competition. The purpose of this study was conduced to find out how much influence wages and incentives on employee productivity. Sampling tech nique using saturated samples,ie all employees PT Indonesia Epson Industry which amounted to 50 people. Analysis techniques used are validity test, reliability test, multiple linear regression analysis, F test and t test. The result of this research shows that based on the equation Y = 23,227 + 1,085 (X1) + 0,200 (X2) F test result that is F count equal to 2,456 with sig. = 0,001. Thus obtained that the hypothesis that the wage and incentives variables together have a significant effect on work productivity.